1993
DOI: 10.1111/j.1095-8312.1993.tb00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Selfing and outcrossing in hermaphrodite freshwater gastropods (Basommatophora): where, when and why

Abstract: Hermaphrodite freshwater snails offer the opportunity to study the evolution of selfing and outcrossing. Laboratory studies using genetic markers have shown that selfing is possible in all species investigated, although outcrossing seems to be favoured in most. Predominance of outcrossing is promoted by sperm storing for up to several months. Studies using electrophoretic markers also suggest that outcrossing is the main breeding system in natural populations. However, heterozygote deficiencies found in some p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(35 citation statements)
references
References 112 publications
(76 reference statements)
1
34
0
Order By: Relevance
“…Indeed, using a more robust method to estimate selfing rates based on microsatellites, David et al (2007) showed that hermaphroditic basommatophoran snails lack individuals that have a mixed breeding system (Escobar et al 2011). This is in line with behavioural studies showing that, although many outcrossing hermaphroditic gastropods may be able to self (Jarne and Delay 1991; Jarne et al 1993), 1) natural populations appear primarily or entirely outcrossing (Jarne and Städler 1995), 2) offspring produced by isolated individuals suffer from strong inbreeding depression (Escobar et al 2011), and 3) individuals immediately switch from self‐fertilization to outcrossing when provided with a partner (reviewed by Jordaens et al 2007). Other species appear to be strictly self‐fertilizing and suffer from strong outbreeding depression (Escobar et al 2011).…”
supporting
confidence: 63%
“…Indeed, using a more robust method to estimate selfing rates based on microsatellites, David et al (2007) showed that hermaphroditic basommatophoran snails lack individuals that have a mixed breeding system (Escobar et al 2011). This is in line with behavioural studies showing that, although many outcrossing hermaphroditic gastropods may be able to self (Jarne and Delay 1991; Jarne et al 1993), 1) natural populations appear primarily or entirely outcrossing (Jarne and Städler 1995), 2) offspring produced by isolated individuals suffer from strong inbreeding depression (Escobar et al 2011), and 3) individuals immediately switch from self‐fertilization to outcrossing when provided with a partner (reviewed by Jordaens et al 2007). Other species appear to be strictly self‐fertilizing and suffer from strong outbreeding depression (Escobar et al 2011).…”
supporting
confidence: 63%
“…Hermaphroditism and self-fertilization are common among the vascular plants (50) but proportionally rarer among animal species. Nevertheless, several animal phyla, such as mollusks, include both dioecious and hermaphroditic groups (51,52) in which it should prove profitable to investigate the evolutionary forces acting on rate of self-fertilization. Testing sex-allocation theory in plants often involves measuring investment in attractive structures and then either assigning a fraction of the investment to male and female function (53) or determining the effects of attraction on success through male function, female function, and self-fertilization (15).…”
Section: Discussionmentioning
confidence: 99%
“…Population data suggest much higher selfing rates in two populations of P. acuta from Lake Geneva ( Monsutti & Perrin, 1999). The sperm transferred during copulation can be stored and used for many weeks (see Jarne et al ., 1993 ; Vianey‐Liaud, 1997). Eggs are laid within a capsule upon available supports (e.g.…”
Section: Methodsmentioning
confidence: 99%